Precipitating and Drying Cement Copper at Kennecott's Bingham Canyon Facility (d99153e6-6508-48ae-be0b-262baadda362) - Joseph W. Schlitt; Bruce P. Ream; Lawrence J. Haug; William D. Southard (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1980)
The operation of Kennecott 's Bingham Canyon copper precipitation plant, one of the world's largest, is described. This description includes a brief historical review of precipitation at Bingham and the general layout and operation of the present cone cementation facility. Current practices are based on results of studies undertaken to define improvements needed in each unit operation. These improvements were required to meet changing plant conditions and were implemented primarily within the constraints of the existing facilities. Specific unit operations included were the cone precipitators, the cone discharge thickener, the cone effluent settling basins, and the plate and frame filter presses. As a result of these improvements, loss of precipitated copper decreased and the degree of precipitation increased, raising copper recovery by 9 t/d. At the same time, iron consumption was reduced by 22.5 t/d. Problems in drying the cement copper were also overcome so that a product containing 12-15% moisture could be consistently delivered for smelting.